THE HANG-GLIDER FLIGHT PLAYFUL CULTURE (Fiep Bulletin - online, 2014)
SUMMARY: this work has as its objective to situate the practice of the hang-glider flight in the universe of games, identifying the playful aspects present in this practice. For that we have analyzed articles and interviews found in a magazine specialized in hang-gliding. It is an exploratory descriptive study, with qualitative approach. The articles and discourses of the interviews of the magazines Air from number 01 to 15 were examined under the form of content analysis (Bardin, 1974). Based on the speeches of those magazines, we can conclude that flying by hang-glider it is an activity that provides a freedom sensation, a rescue of spontaneity, a pleasure in the playful sense. It is a game full of adventure that looks for the vertigo exposing the pilot to a calculated risk.
Keywords: free flight; game; sport in the nature